If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(2x-3)-x=x+1
We move all terms to the left:
2(2x-3)-x-(x+1)=0
We add all the numbers together, and all the variables
-1x+2(2x-3)-(x+1)=0
We multiply parentheses
-1x+4x-(x+1)-6=0
We get rid of parentheses
-1x+4x-x-1-6=0
We add all the numbers together, and all the variables
2x-7=0
We move all terms containing x to the left, all other terms to the right
2x=7
x=7/2
x=3+1/2
| 3.2-5=z | | X=210-2x= | | 13+6x=-2 | | x-0.2x=15000 | | Z=y-3.2 | | 4(2x-3)-2x=11 | | 15+6x-8x=0 | | 4(x-1)=3-x+2(x+5) | | 11-x/6=11 | | (3t+6)-7t+42=0 | | х^4-2х^3-4x+4=0 | | X^4-6x^2+12=0 | | 2x/6+x-5/2=x-2 | | 3+10x=7/x | | x/28=0.4 | | 1+0,3x+2+0,2x=40 | | 12x-16=4x+16 | | 4x+16=12x-16 | | 4x+16=11x-8 | | 7m+18=11m-6 | | 3×-8y+17=0 | | 9x=8*16 | | 2x+4(3x+6)+2=-8x | | C=25h+100 | | x^2-3x=3=0 | | 21y+30=12 | | 4yy=3 | | 3yy=-7 | | 22+x=33 | | (2^2)x-4+x=8 | | 5x-36=4x-30 | | X+1=3-4x |